Comparison of novel large‐bore and conventional‐bore covered self‐expandable metal stents for malignant gastric outlet obstruction: Multicenter, retrospective study. Issue 1 (12th September 2022) - Inokuma, Akiyuki; Takahara, Naminatsu; Ishibashi, Rei; Hakuta, Ryunosuke; Ishigaki, Kazunaga; Saito, Kei; Saito, Tomotaka; Hamada, Tsuyoshi; Mizuno, Suguru; Yagioka, Hiroshi; Takahashi, Sho; Kogure, Hirofumi; et al.
Abstract : Objectives: Covered self‐expandable metal stent (cSEMS) for gastric outlet obstruction (GOO) has been developed to overcome tumor ingrowth but is prone to be associated with an increased risk of migration. Clinical impact of the novel large‐bore cSEMS for malignant GOO remains unclear. Methods: A total of 117 patients undergoing endoscopic cSEMS placement for malignant GOO were enrolled in this multicenter retrospective study. Technical and clinical success, adverse events, recurrent GOO, and survival after stent placement were compared between 24 mm‐cSEMS ( n  = 49) and 20 mm‐cSEMS ( n  = 68). Results: Patient characteristics were well‐balanced and thus similar survival was observed between the two groups (136 days vs. 89 days, P  = 0.60). Technical success rate of 100% and clinical success rate of 96% were achieved both in 24 mm‐cSEMS and 20 mm‐cSEMS, respectively. The median cumulative time to recurrent GOO was significantly longer in 24 mm‐cSEMS than in 20 mm‐cSEMS (380 days vs. 138 days, P  = 0.01). The incidence of adverse events and recurrent GOO was comparable: 12% vs. 15% ( P  = 0.91), and 16% vs. 31% ( P  = 0.11); however, no stent migration was observed in 24 mm‐cSEMS. In a subgroup analysis, the superiority of 24 mm‐cSEMS to 20 mm‐cSEMS was demonstrated in extrinsic cancers (380 days vs. 121 days, P  = 0.01) but not in intrinsic cancers (151 days vs. not reached, P  = 0.47). Conclusions: The 24 mm‐cSEMS may improve time to recurrent GOO with ensuring acceptable safety in patients with malignant GOO.